Pelatihan Manajemen Risiko Digital Untuk Menciptakan Lingkungan Aman Dan Produktif Di Madrasah Ibtidaiyah Al–Ibrohimy - Abu Siri (Pusat Penelitian dan Pengabdian Masyarakat STIQ ZAD Cianjur, 2026)
The rapid development of digital technology in educational environments presents both opportunities and risks for students, including misuse of personal data, cyberbullying, and exposure to negative online content. This condition highlights the importance of strengthening digital literacy and security awareness within madrasah settings. This community service program aimed to enhance teachers’ understanding of digital risk management in order to create a safe and productive learning environment. The program was conducted at Madrasah Ibtidaiyah Al-Ibrohimy Galis and involved 14 teachers. The implementation employed a participatory approach consisting of needs analysis, training and workshops, as well as mentoring and evaluation. The training materials covered digital risks, data security, digital ethics, and cyberbullying prevention. Evaluation was conducted through pre-tests, post-tests, observations, and reflective discussions. The results showed a significant improvement in teachers’ understanding of digital risks, with the average score increasing from 58 in the pre - test to 84 in the post - test. In addition, the program produced a digital security Standard Operating Procedure (SOP) for the madrasah as a guideline for safe and responsible technology management. These findings indicate that participatory-based training is effective in strengthening digital literacy and digital security governance in primary education.